(untitled) (Swiss Medical Weekly, 2021)
Approximately 420 men are diagnosed with germ-cell cancer (GCC) in Switzerland each year. Recent international guidelines outline management issues, but many aspects remain controversial in an area of highly individualised treatments. Even more than in other tumour types, in GCC the challenge is to choose exactly the correct treatment for an individual patient. Overtreatment in patients likely to be cured must be avoided to reduce long-term toxicities. On the other hand, treatment intensification is required in patients presenting with adverse prognostic factors. Therefore, referral to expert centres or consultations with an expert for a second opinion is strongly recommended. In 2020, Swiss experts discussed their strategies in a consensus meeting during the virtual Swiss Oncology and Haematology Congress (SOHC) in order to harmonise their concepts and to suggest optimal strategies for the management of GCC patients in Switzerland. Votes on controversial issues were obtained and are presented in this review wherever applicable.